2018
DOI: 10.1002/ccd.27944
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of angiographic thrombus burden and impact of thrombus aspiration on outcome in young patients with ST‐segment elevation myocardial infarction

Abstract: Objectives We aimed to investigate the determinants of thrombus burden (TB) and the impact of thrombus aspiration (TA) on outcome in young adults with ST segment elevation myocardial infarction (STEMI). Background The determinants of TB in young STEMI patients are not fully understood now. Methods The 182 young (age ≤ 45 years) STEMI patients, who underwent coronary angiography and percutaneous coronary intervention (PCI) in our hospital from January 2013 to September 2016, were included. Angiographic TB and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Similar to our finding, a study done during 2016 showed that the top three significant positive correlated variables for longer LOS were patients with heart failure, who were older and female [32]. It was consistent with the findings about factors related to prolonged LOS from literature: female, increasing age, and comorbidities such as cerebrovascular disease and diabetes mellitus [33,36].…”
Section: B: Coronary Artery Extentsupporting
confidence: 92%
“…Similar to our finding, a study done during 2016 showed that the top three significant positive correlated variables for longer LOS were patients with heart failure, who were older and female [32]. It was consistent with the findings about factors related to prolonged LOS from literature: female, increasing age, and comorbidities such as cerebrovascular disease and diabetes mellitus [33,36].…”
Section: B: Coronary Artery Extentsupporting
confidence: 92%
“…In addition, our study found that the time from SO-to-FMC and D2B was longer in STEMI patients with COVID-19 than in those without COVID-19. The studies of Duman et al ( 44 ) and Ge et al ( 45 ) reported that the delay in SO-to-FMC and D2B would prolong the time for opening infarct-related vessels which may account for a higher thrombus burden. Therefore, in the COVID era, it is of great significance that novel technologies should be developed so as to achieve more efficient thrombus aspiration in patients with very high intra-coronary thrombus burden such as patients with STEMI and coexistent COVID-19 infection ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“… 13 In addition, TA reduced the incidence of MACE by more than half, including cardiac mortality, recurrent MI, stroke, coronary artery bypass graft, and repeat PCI in STEMI adults with a high thrombus burden. 9 Recent prospective randomization clinical trials confirmed that TA improved myocardial perfusion but failed to improve the prognosis, possibly because of the short follow-up period. 8 While several studies indicated that TA during PPCI was not associated with a better clinical prognosis, 14 16 a meta-analysis reported that patients with a high thrombus burden received the highest potential benefit from TA.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the hypothesis that patients with a higher thrombus burden may benefit from TA, recent studies showed that TA can better improve myocardial reperfusion in patients with STEMI and a high thrombus load and significantly decrease the cumulative major adverse cardiac events (MACE) rate of the 1-year outcome. 8 , 9 However, both the TASTE and TOTAL trials did not show a benefit in the primary outcome for patients with a high thrombus burden. 6 , 7 To date, the benefit of TA for patients with large thrombus burden remains controversial.…”
Section: Introductionmentioning
confidence: 99%